The Health/Care Divide: Breastfeeding in the New Millenium - Laufer-Ukeles, Pamela; Barzilay, Arianne Renan (Columbia Journal of Gender and Law, 2018)
Given recent health and cultural pressures to breastfeed, this Article argues that legal and societal developments should enable working mothers to choose whether or not to breastfeed without sacrificing their employment. In analyzing current solutions for working mothers, we identify two major developments, which we term “separation strategies,” to contend with the health push: limited and unpaid pumping breaks at work established by the Patient Protection and Affordable Care Act and the advent of an online market in human milk. We critique these developments, despite the limited relief they may provide, for the way these strategies do not provide sufficient breastfeeding support and separate the nurturing act of breastfeeding from the nutritional benefits believed to be contained in breastmilk as a sole recourse for working women. Separation strategies reflect the legal and societal undervaluing of direct, symbiotic parental care and the way scientific priorities tend to separate and sterilize nutritional and relational benefits while overlooking additional health benefits of the breastfeeding method, as well as the cost, threats to breastmilk supply, and distributive effects of separation strategies. We describe the way legislative measures, antidiscrimination law, and constitutional rights have failed to aid breastfeeding mothers in the workplace. Finally, we articulate ways in which the workplace can be restructured to accommodate breastfeeding and, as a result, parental care more generally.